2015
DOI: 10.1177/1759091415568913
|View full text |Cite
|
Sign up to set email alerts
|

Myelin Abnormalities in the Optic and Sciatic Nerves in Mice With GM1-Gangliosidosis

Abstract: GM1-gangliosidosis is a glycosphingolipid lysosomal storage disease involving accumulation of GM1 and its asialo form (GA1) primarily in the brain. Thin-layer chromatography and X-ray diffraction were used to analyze the lipid content/composition and the myelin structure of the optic and sciatic nerves from 7- and 10-month old β-galactosidase (β-gal) +/? and β-gal −/− mice, a model of GM1gangliosidosis. Optic nerve weight was lower in the β-gal −/− mice than in unaffected β-gal +/? mice, but no difference was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 96 publications
0
9
0
Order By: Relevance
“…Interestingly, pharmacological supplementation of PD patients with GM1a has been shown to have beneficial effects on clinical motor and neuropsychological functions in a 5-year study ( Schneider et al, 2010 ). Curiously, in addition to having essential functions in membrane lipid rafts ( Schnaar, 2016 ), GM1a is enriched in myelin ( Heinecke et al, 2015 ) and the GM1a increase observed here may reflect age-related changes in myelin structures.…”
Section: Discussionmentioning
confidence: 84%
“…Interestingly, pharmacological supplementation of PD patients with GM1a has been shown to have beneficial effects on clinical motor and neuropsychological functions in a 5-year study ( Schneider et al, 2010 ). Curiously, in addition to having essential functions in membrane lipid rafts ( Schnaar, 2016 ), GM1a is enriched in myelin ( Heinecke et al, 2015 ) and the GM1a increase observed here may reflect age-related changes in myelin structures.…”
Section: Discussionmentioning
confidence: 84%
“…An increase in G M1 and G A1 was found in the CNS of the current Glb1 −/− mice as well as in the CNS [24,58], optic and sciatic nerves [126] and in the retina [125] of other Glb1 knockout mouse models. Moreover, the increase in phosphatidylserine in the CNS of the current Glb1 −/− mice resembles the findings of Heinecke et al (2015) in the optic nerve [126]. Nevertheless, current Glb1 −/− mice also revealed accumulations of sphingomyelin and phosphatidylcholine, which might stabilize cell membrane integrity.…”
Section: Discussionmentioning
confidence: 82%
“…Recent literature has addressed the role of myelin pathology in GM1 and other neuropathic LSDs. Studies involving children, 24,126,128 dogs, 144 mice, 145 and cats 146 with GM1 have universally reported decreased myelin in the CNS, with a reduction in Luxol Fast Blue staining being the most commonly reported evidence of this pathology. 24,126,146 Some studies have measured myelin using X-ray diffraction 145 or noted ultrastructural abnormalities with transmission electron microscopy (TEM) such as fewer myelinated axons 126 and unraveling of myelin sheaths (Figure 1A and B).…”
Section: Myelin Pathologymentioning
confidence: 99%
“…Studies involving children, 24,126,128 dogs, 144 mice, 145 and cats 146 with GM1 have universally reported decreased myelin in the CNS, with a reduction in Luxol Fast Blue staining being the most commonly reported evidence of this pathology. 24,126,146 Some studies have measured myelin using X-ray diffraction 145 or noted ultrastructural abnormalities with transmission electron microscopy (TEM) such as fewer myelinated axons 126 and unraveling of myelin sheaths (Figure 1A and B). 146 The mechanism(s) behind myelin abnormalities and their effects on disease pathogenesis is an emerging discussion topic in the literature, with three main hypotheses considered: dysmyelinogenesis (failure to form myelin properly), primary demyelination (dysfunction or destruction of myelin after proper formation), or secondary demyelination (due to axonal degeneration).…”
Section: Myelin Pathologymentioning
confidence: 99%